Novel insights into ascorbic acid skin permeation - Mistry, Jatin (2020)
Ascorbic acid (vitamin C) is a popular topically applied cosmeceutical due to its antioxidative, photoprotective, antiaging and antipigmentary effects. Despite these beneficial effects to the skin, instability of ascorbic acid in aqueous solution has directed formulation scientists to focus on stable ascorbic acid derivatives that can be used in topical preparations. However, these derivatives are required to be metabolised by the skin to the active, free-acid form to observe efficacy. Accordingly, current knowledge regarding skin permeation of ascorbic acid is limited, with in vivo human skin permeation data unavailable.